2001
DOI: 10.1016/s0305-1978(00)00031-4
|View full text |Cite
|
Sign up to set email alerts
|

Character coding of secondary chemical variation for use in phylogenetic analyses

Abstract: A coding procedure is presented for secondary chemical data whereby putative biogenetic pathways are coded as phylogenetic characters with enzymatic conversions between compounds representing the corresponding character states. A character state tree or stepmatrix allows direct representation of the secondary chemical biogenetic pathway and avoids problems of non-independence associated with coding schemes that score presence/absence of individual compounds. Stepmatrices are the most biosynthetically realistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
36
0
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 42 publications
2
36
0
3
Order By: Relevance
“…In addition to their ecological significance, floral fragrances have been recognized as chemotaxonomic markers in some plant taxa (Gerlach and Schill, 1989;Dahl et al, 1990;Harborne, 1993;Knudsen, 1994;Knudsen and Mori, 1996). Floral odor compounds are somewhat limited markers however, due to homoplasy and high intraspecific variation (see Williams and Whitten, 1999;Azuma et al, 2001;Barkman, 2001;Levin et al, 2001).…”
mentioning
confidence: 99%
“…In addition to their ecological significance, floral fragrances have been recognized as chemotaxonomic markers in some plant taxa (Gerlach and Schill, 1989;Dahl et al, 1990;Harborne, 1993;Knudsen, 1994;Knudsen and Mori, 1996). Floral odor compounds are somewhat limited markers however, due to homoplasy and high intraspecific variation (see Williams and Whitten, 1999;Azuma et al, 2001;Barkman, 2001;Levin et al, 2001).…”
mentioning
confidence: 99%
“…An objection to the use of floral scent patterns in systematics is that convergence of floral scents may play an important role in plants in general, caused by similar pollinator pressures acting on plants of independent origin (Dobson et al, 2005). Nevertheless, comparative studies of floral scent and DNA data in orchids (Barkman, 2001;Williams and Whitten, 1998) as well as in Nyctaginaceae (Levin et al, 2003) revealed that the tree topologies generated by non-coding DNA markers are in some cases congruent with those based on floral scent data.…”
Section: Introductionmentioning
confidence: 97%
“…The methods to analyse scent patterns for taxonomical questions are manifold (Barkman, 2001;Levin et al, 2003). The simplest method is the use of presence/ absence data of different flower volatiles.…”
Section: Introductionmentioning
confidence: 99%
“…Seaman e Funk (1983) desenvolveram um método para codificar a presença e a ausência de determinada via metabólica e de cada substância dentro da via. Barkman (2001) propôs a utilização da via biossintética como caráter e das suas conversões enzimáticas como estados de caráter.…”
Section: Alcaloides Benzilisoquinolínicos Apoiaram Reformulações Da Cunclassified
“…Como as substâncias de uma dada via estão relacionadas e dependem umas das outras durante o processo de biossíntese, elas não podem ser definidas como caracteres. É mais adequado que sejam consideradas estados de um caráter, nesse caso a própria via em que são produzidas (Barkman, 2001). …”
Section: Alcaloides Benzilisoquinolínicos Apoiaram Reformulações Da Cunclassified